Energy Consumption Minimization for Autonomous Mobile Robot: A Convex Approximation Approach - Van, Nguyen Thi Thanh; Tien, Ngo Manh; Luong, Nguyen Cong; Duyen, Ha Thi Kim (Journal of Robotics and Control (JRC), 2023)
In this paper, we consider a trajectory design problem of an autonomous mobile robot working in industrial environments. In particular, we formulate an optimization problem that jointly determines the trajectory of the robot and the time step duration to minimize the energy consumption without obstacle collisions. We consider both static and moving obstacles scenarios. The optimization problems are nonconvex, and the main contribution of this work proposing successive convex approximation (SCA) algorithms to solve the nonconvex problems with the presence of both static and moving obstacles. In particular, we first consider the optimization problem in the scenario with static obstacles and then consider the optimization problem in the scenario with static and moving obstacles. Then, we propose two SCA algorithms to solve the nonconvex optimization problems in both the scenarios. Simulation results clearly show that the proposed algorithms outperform the A* algorithm, in terms of energy consumption. This shows the effectiveness of the proposed algorithms.